2017
DOI: 10.3127/ajis.v21i0.1438
|View full text |Cite
|
Sign up to set email alerts
|

Threats to Autonomy from Emerging ICTs

Abstract: This paper examines threats to autonomy created by significant emerging ICT's. Emerging ICT's cover a wide range of technologies, from intelligent environments to neuroelectronics, yet human autonomy is potentially threatened by all of them in some way. However, there is no single agreed definition of autonomy. This paper therefore considers the ways in which different versions of autonomy are impacted by different systems. From this range of threats we will derive some properties which any ICT must exhibit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Methods of the impact of various information and communication technologies on the safety of economic agents are shown in [21]. However, in this work there are no parameters for the degree of such influence on the information security of the subjects of the information infrastructure.…”
Section: Issn 2226-3780mentioning
confidence: 96%
“…Methods of the impact of various information and communication technologies on the safety of economic agents are shown in [21]. However, in this work there are no parameters for the degree of such influence on the information security of the subjects of the information infrastructure.…”
Section: Issn 2226-3780mentioning
confidence: 96%
“…However, there are many different definitions of autonomy (Dainow, 2017b). The term was initially restricted to morality by Kant, who argued that all humans had the innate capacity to determine what was morally right and wrong (Kant, 1998).…”
Section: Ethics and The Three Modes Of The Integrated Nodementioning
confidence: 99%
“…Here the focus lies on the internal processes by which one exercises autonomy. The general concerns are to distinguish the degree of external influence which can be allowed before we can say autonomy has been lost and what, if any, specific cognitive elements are required in order for self-reflection to count as autonomous (Dainow, 2017b). Even the same definition of autonomy can lead to people living incompatible lives because they hold different values.…”
Section: Ethics and The Three Modes Of The Integrated Nodementioning
confidence: 99%
See 1 more Smart Citation
“…Information systems research has shown the importance of values in systems design thinking in many areas, including online applications (Chesney, Coyne, Logan, & Madden, 2009;Friedman, Nathan, & Yoo, 2016), sensor development (Dechesne, Warnier, & van den Hoven, 2013), areas of eHealth (Boonstra & Van Offenbeek, 2010), emerging technologies (Dainow, 2017;Poulsen, 2018b) and other areas (Burmeister, 2013;Burmeister, Islam, Dayhew, & Crichton, 2015). However, to date little research has investigated values in the design of care robots.…”
Section: Care Valuesmentioning
confidence: 99%